Loss of RHBDF2 results in an early-onset spontaneous murine colitis. Issue 4 (29th January 2019) - Geesala, Ramasatyaveni; Schanz, Willow; Biggs, Mikayla; Dixit, Garima; Skurski, Joseph; Gurung, Prajwal; Meyerholz, David K; Elliott, David; Issuree, Priya D; Maretzky, Thorsten
Abstract: Inflammatory bowel disease (IBD) is a heterogeneous group of inflammation-mediated pathologies that include Crohn's disease and ulcerative colitis and primarily affects the colon and small intestine. Previous studies have shown that a disintegrin and metalloprotease (ADAM) 17, a membrane-bound sheddase, capable of cleaving the proinflammatory cytokine TNF and epidermal growth factor receptor ligands, plays a critical role in maintaining gut homeostasis and modulating intestinal inflammation during IBD. Rhomboid 5 homolog 2 (RHBDF2), a catalytically inactive member of the rhomboid family of intramembrane serine proteases, was recently identified as a crucial regulator of ADAM17. Here, we assessed the role of RHBDF2 in the development of colitis in the context of IL10 deficiency. Il10 −/− / Rhbdf2 −/− mice developed spontaneous colitis and experienced severe weight loss starting at 8 wk of age, without the need for exogenous triggers. Severity of disease pathology in Il10 −/− / Rhbdf2 −/− mice correlated with a dysbiotic gut microbiota and elevated Th1-associated immune responses with increased interferon gamma and IL2 production. In addition, Il10 −/− / Rhbdf2 −/− mice failed to maintain their epithelial cell homeostasis, although the intestinal epithelial barrier of Rhbdf2 −/− mice is intact and loss of Rhbdf2 did not significantly exacerbate sensitivity to dextran sulfate sodium-induced colitis, suggesting differences in the underlying disease pathway of intestinal inflammation in this model. Taken together, our results demonstrate a critical regulatory role for RHBDF2 in the maintenance of the unique homeostasis between intestinal microbiota and host immune responses in the gut that is dysregulated during the pathogenesis of IBD. Graphical Abstract: RHBDF2 participates in maintaining the critical balance between intestinal microbiota and host immune responses during the pathogenesis of colitis in Il10 -deficient mice.